High-Resolution Compact On-Chip Spectrometer Based on an Echelle Grating With Densely Packed Waveguide Array - Keqi Ma; Kaixuan Chen; Ning Zhu; Liu Liu; Sailing He (IEEE Photonics Journal)
We design a 121-channel on-chip spectrometer based on an echelle grating with densely packed waveguide array on 220-nm silicon-on-insulator platform. It offers a high spectral resolution of 0.5 nm in a 3 * 3 mm2 footprint, covering a spectral range of 60 nm near the central wavelength of 1550 nm. We fabricate the spectrometer with 20 channels for verification of the design, which is limited by our equipment. The measured crosstalk for the fabricated device is –4.3 dB and can be improved by better fabrication techniques. This spectrometer can be used for lab-on-a-chip spectroscopy applications, such as drug analysis in biotechnological and pharmaceutical research.